UNITED PARTY TRANSVAAL Inventory of documents - UNITED PARTY TRANSVAAL (ARCA, 2018)
Papers of UP Transvaal. In December 1934 the National Party and the South African formed a coalition to become the United South African National Party known as the United Party.
COVERAGE 1953-1974; 7 Files; 0,11 Metres.
Keywords: UNITED PARTY TRANSVAAL; Inventories; Politicians